Short Communication: Phenotypic diversity of male Burgo chicken from Bengkulu, Indonesia - JOHAN SETIANTO; SUTRIYONO SUTRIYONO; HARDI PRAKOSO; BASYARUDDIN ZAIN; RIFKY ADWIYANSYAH; AMIR HUSAINI KARIM AMRULLAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Setianto J, Sutriyono, Prakoso H, Zain B, Adwiyansyah R, Amrullah AHK. 2019. Short Communication: Phenotypic diversity of male Burgo chicken from Bengkulu, Indonesia. Biodiversitas 20: 532-536. Burgo chicken is the result of a crossbreed of Red Junglefowl (Gallus gallus gallus) with Kampung chicken (Gallus domestica). This study aimed to describe the diversity of colors found in male Burgo chickens. The study was conducted in the city of Bengkulu, Indonesia. The method used in this study was a direct observation of the 50 male chickens on the breeders. The breeders belonging to the Burgo chicken community were determined by random sampling method. The breeders who did not join the community were determined by the snowball sampling method. This method was carried out because the presence of breeders who keep Burgo chickens was unknown. The data in this study consisted of the color of chest feathers, neck feathers, wing feathers, tail feathers, saddle feathers, and the number of wing and tail feathers. The data obtained were analyzed descriptively. The number of colors ranges 4 to 11 with the high diversity is mainly found on the feathers of the chest, neck and, saddle.